Unna Thost Keratoderma palmoplantar . A Case Report - Graciela Caridad Cabrera Acea; María Teresa Rodríguez Gandulla; Niurka Ramos Viera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
The case of a 37 years old, black skinned, male patient who attended Dermatology Consultation in his health area is presented. The patient had skin lesions on the palms of his hands and the soles of his feet. He stated that these injuries had worsened with time. Eventually they became hyperkeratotic lesions affecting the knuckles and the knees. The patient also presented a deformity of his fingernails resembling a parrot's beak that produced pain and moderate hyperhidrosis. A diagnosis of diffuse orthokeratotic Thost-Unna keratoderma was completed. This keratoderma occurs in one out of every 40 000 people and is hereditary. Because it is such an uncommon presentation with biological implications, psychological impact and work impediments, that requires a specific medical monitoring, it was decided to present this case to be published.